Implementation of E-Money as Student Payment at Al-Amien Islamic Boarding School from an Islamic Economic Perspective - Syaifullah Syaifullah; Rudy Haryanto; Agoes Kamaroellah (Institut Dirosat Islamiyah Al-Amien Prenduan Sumenep, 2024)
Humans, as social beings, are required to constantly innovate in economic activities, especially in the use of digital technology, particularly during the COVID-19 pandemic. Currently, cashless payment systems or e-money have become a solution to the demands of the times. This includes SMA Tahfidh Al-Qur’an PP. Al-Amien Prenduan, which also implements e-money as a payment tool in transactions within the PP. Al-Amien Prenduan environment. This is what prompted the researcher to delve deeper into the implementation of e-money as a student payment tool from an Islamic perspective. The research problems are: how is the implementation of e-money as a student payment tool from an Islamic perspective, and what are its impacts on students, guardians, and the boarding school? This research uses a qualitative approach at SMA Tahfidh Al-Qur'an PP. Al-Amien Prenduan. Data collection was carried out through direct field observations, semi-structured interviews, and documentation methods with all related sources. Data analysis was performed using the Miles, Huberman, and Saldana theoretical model. The results show that the implementation of e-money as a student payment tool runs as expected by all parties and has a positive impact on everyone at PP. Al-Amien Prenduan. For example, students do not lose money, it prevents corruption, and it facilitates guardians when sending money, and students no longer have to wait in long lines when shopping at the boarding school-owned business units. From an Islamic perspective, the implementation of e-money as a student payment tool is allowed according to the sharia contracts that occur when transacting based on evidence from the Qur'an and Hadith, except if there is maysir (gambling), riba (usury), gharar (uncertainty), and haram (prohibited) elements in the e-money implementation. This research provides a perspective on the use of e-money as a payment tool in boarding schools or other educational institutions.